The Council of Europe Commissioner for Human Rights and the European Court of Human Rights: An ever-closer relationship - Mijatović, Dunja; Weber, Anne (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2020)
The relationship between the Commissioner for Human Rights and the European Court of Human Rights has varied considerably over time, from a clear separation of functions to increasing interactions. Resolution (99)50 on the Council of Europe Commissioner for Human Rights, adopted on 7 May 1999, reflects a clear willingness to separate the two institutions. This separation, however, did not mean isolation from each other in practice and did not prevent cross-references between the Commissioner and the Court from increasing over the years. In the course of his/her country or thematic work, the Commissioner relies on international and European conventions, and in the first place the Convention and the case law of the Court, when making recommendations to member states. Conversely, the Court has from the outset made references to the work of the Commissioner in its judgments. While the different roles of the two institutions might explain the sometimes diverging approaches, cross-references between the Commissioner and the Court have undoubtedly enriched each other’s work. With the entry into force of Protocol nº14 to the Convention in 2010, the Commissioner’s functions have been formally extended, providing formal recognition to the institution of the Commissioner, which is expressly introduced in the text of the Convention and into the control mechanism established by the Convention. The Commissioner may now on his/her own initiative exercise the right to intervene as a third-party before the Court, by submitting written comments and taking part in hearings. This possibility represents an additional tool at the Commissioner’s disposal to help promote and protect human rights. The Commissioner’s role in the process of execution of the Court’s judgments has also increased over the years. With the amendment introduced in 2017 to the Rules of the Committee of Ministers for the supervision of the execution of judgments (Rule 9), which allows the Commissioner to submit written comments on the execution of judgments directly to the Committee of Ministers, the contribution by the Commissioner to the execution of judgments is expected to have a greater impact.